One Health approach to Coxiella burnetii in Brazilian indigenous communities - Farinhas, João Henrique; de França, Danilo Alves [UNESP]; Serpa, Maria Carolina; Biondo, Leandro Meneguelli; Doline, Fernando Rodrigo; Giuffrida, Rogério; Santarém, Vamilton Alvares; dos Santos, Andrea Pires; Labruna, Marcelo B.; Kmetiuk, Louise Bach; Biondo, Alexander Welker (My University, 2024)
Indigenous health has posted complex challenges worldwide, particularly due to historical economic, territorial, social and environmental processes, which may lead to emergence and reemergence of pathogens. In addition to few Coxiella burnetii serosurveys in vulnerable populations, especially in developing tropical countries, no comprehensive One Health approach has focused on human-animal infection along with potential environmental determinants. Accordingly, this study aimed to assess the seroprevalence of anti-C. burnetii antibodies in indigenous populations and their dogs from 10 indigenous communities distributed in southern and southeastern Brazil, along with the correspondent healthcare professionals. In overall, 8/893 (0.90%; 95% CI 0.45–1.76) indigenous and 1/406 (0.25%) dog samples were seropositive, with 7/343 (2.04%) individuals the 1/144 (0.69%) dog from the Ocoy community, located in the city of São Miguel do Iguaçu, bordering Argentina at south, and far 10 km at west from Paraguay. All 84 healthcare professionals tested seronegative.